Work and social inequalities in health in Europe (Brussels, 2007)
"Equity in health is endorsed by most governments. But there is no progress in reducing the relative differences between different socioeconomic groups linked to the professional status. There are obvious reasons for class differences that include poverty, low education and certain life style factors. But do we know the true background of the differences? Why do blue-collar workers have less favourable health than white-collar workers? Is it due to selection of unhealthy workers to bad workplaces or due to the working conditions? This volume provides an overview of the importance of working conditions for social class differences in health. The magnitude of social class differences in health and the importance of working conditions for these differences are described for seven European countries and Massachusetts, USA. In a summary chapter conclusions are drawn regarding to what extent social class differences in health can be explained by working conditions. An agenda for future research is presented. "